Association of growth hormone gene polymorphism with bodyweight Kampung chicken - Muqsita Rahmat; Depison Depison; Eko Wiyanto (Universitas Sebelas Maret, 2022)
Objective: The study's goal was to obtain growth hormone gene polymorphism and association growth hormone gene polymorphism with bodyweight Kampung chicken.Methods: The research material is 50 samples of blood from Kampung chickens aged three months. The method used was included: DNA ektraksi, amplification PCR, characterization and identification using PCR-RFLP with the enzyme MspI. The data collected is of a frequencies genotype and allele. The locus was polymorphic, equilibrium population on the diversity of the gene GH MspI association with body weight at three months of age was an analysis using the mean difference test.Results: Gene GH MspI of Kampung chicken polymorphic, the gene GH of Kampung chicken is in a population imbalance, gene GH MspI of Kampung chicken has a diversity very informative and has an association polymorphic on the genotype A2A2 significant (P<0.05) with bodyweight Kampung chickens aged three months.Conclusions: Gene GH MspI of Indonesian chicken has an association with body weight aged three months, polymorphic, and can be used as a reference in making selections to improve genetic quality.